AB0112 Anticytokine, Antioxidant and Anti-Inflammatory Action of Spironolactone in Collagen Induced Arthritis: Candidature of Spironolactone as a Novel DMARD. (10th June 2014) - Syngle, A.; Verma, I.; Krishan, P.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune and chronic inflammatory condition with evolving treatment strategies. Pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-6, and oxidative stress markers such as nitric oxide (NO), thiobarbituric acid reactive substances (TBARS), activity of superoxide dismutase (SOD) and levels of glutathione (GSH) are mediators in RA pathogenesis. Inhibitory effects of these cytokines production and oxidative stress have been attributed to spironolactone (SPIR). Objectives: To investigate the effect of spironolactone on the inflammatory response with collagen induced arthritis (CIA). Methods: CIA was induced in DBA/1J mice by an intradermal injection of 50 μl of an emulsion of bovine type II collagen (CII; 100μg) in Freund's Complete Adjuvant (CFA) at the base of the tail. On day 21, a booster injection of CII in Incomplete Freund's Adjuvant (IFA) was administered. SPIR (20 mg, 40 mg and 80 mg/kg/day or vehicle (0.5% CMC) and methotrexate (MTX) (5 mg/kg/week) or vehicle PBS was administered beginning on day 21 (arthritis onset) until day 42 to different groups of study mice. Clinical, biochemical estimation of TNF-α, IL-6, oxidative markers and histopathological score were performed at the end of the study. Results: Mice immunized with CII in CFA and IFA developed inflammatory arthritis. SPIR 40, SPIR 80 and MTX treatment significantly (p<0.05, p<0.01and p<0.001 respectively) reduced paw swelling. SPIR 80 and MTX groups had shown marked reduction in arthritis score (p<0.05) but not in SPIR 40 and 20 as compared with positive control mice (Fig.1C ). Consistent with macroscopic scoring, treatment of mice with SPIR40, SPIR 80 and MTX, significantly decreased the concentration of TNF-α and IL-6 (Fig. 1A & 1B ). Surprisingly, SPIR 80 had marked reduction on TNF-α level as compared to MTX treated mice (Fig. 1A ). The degree of oxidative stress significantly (p<0.05) reduced in SPIR 40 and 80 treated mice, as indicated by reduced nitrite levels and TBARS levels, increased SOD and GSH level. In MTX-treated arthritic mice, we observed a significant reduction in the levels of NO (p<0.05) and no significant difference in markers of oxidative stress such as TBARS, SOD and GSH. Histopathological features of CIA included destruction of cartilage at the joint margins. SPIR 80 and MTX treatment significantly (p<0.05) improved the histologic findings in the joint but not in SPIR 20, 40 and placebo groups. Conclusions: First experimental study to investigate the impact of SPIR in CIA model. The study results demonstrate that SPIR exerts inhibition of inflammatory cytokines, reduction in oxidative stress, anti-inflammatory effect on disease which contribute to its anti-arthritic effect. The histopathological improvement and cartilage protection with SPIR provide further evidence of this concept. SPIR through its anti-inflammatory cytokine and antioxidant effect exerts anti-inflammatory and chondroprotective effect in RA. Thus SPIR may have a disease modifying role in RA. Acknowledgements: This study has been supported by a Research Fellowship from University Grant Commission, New Delhi [No. F.10-15/2007 (SA-I)]. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5010